2011
DOI: 10.1007/s10096-011-1373-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of Salmonella sp. by means of a combination of selective enrichment broth and MALDI-TOF MS

Abstract: The identification of Salmonella sp. in stool samples usually takes 2 days when employing routine procedures. Fast approaches are necessary in order to shorten the analysis time. The aim of this work was the development of a rapid procedure for the detection of Salmonella sp. from clinical stool samples. Spiked stool samples were cultured in selective selenite enrichment broth. Identifications were directly performed from the liquid broth by the MALDI Biotyper. After the evaluation of this method, the same pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 29 publications
2
22
0
2
Order By: Relevance
“…Identification of Salmonella on the genus level by classical MALDI biotyping was reported earlier by Sparbier and colleagues (26). In the present study, the identification was correct on the species level; however, the results were inconsistent on the subspecies level, the spectra being too similar to consistently distinguish the three S. enterica subspecies (Fig.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Identification of Salmonella on the genus level by classical MALDI biotyping was reported earlier by Sparbier and colleagues (26). In the present study, the identification was correct on the species level; however, the results were inconsistent on the subspecies level, the spectra being too similar to consistently distinguish the three S. enterica subspecies (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Protein extraction was performed in accordance with a procedure previously described (18) and lately applied by many research groups (19)(20)(21)(22)(23)(24)(25)(26). For classical biotyping, which uses undigested cell extracts, Salmonella enterica subsp.…”
Section: Bacterial Culture and Protein Extraction (Classical Biotyping)mentioning
confidence: 99%
“…An examination of this enrichment method followed by MALDI-TOF MS on 4,847 routine clinical specimens found that of the 108 Salmonella-positive specimens identified by traditional biochemical analysis, MALDI-TOF MS identified 100 of them correctly 24 h earlier. The 8 specimens missed by MALDI-TOF MS could be identified as Salmonella positive only after plating of the enrichment medium, indicating that the bacterial concentration was likely too low to be detected by MALDI-TOF MS (165).…”
Section: The Enterobacteriaceaementioning
confidence: 99%
“…The broad coverage of bacterial species enables such early identification not only for the frequently occurring but also rare pathogens. To combine growth in selective enrichment broth and MALDI-TOF MS identification may help rapid identification of epidemiologically important carriage of Salmonella [18].…”
Section: How Maldi-tof Mass Spectrometry Can Aid Diagnosis Of Hard-tomentioning
confidence: 99%